HYPOCRISY AND GEOPOLITICAL GAMES IN THE FIGHT AGAINST TERRORISM IN THE SAHEL. RETHINKING COUNTERTERRORISM STRATEGIES - PITOKI, Agnazoulèlou (Revue Internationale du Chercheur, 2025)
Abstract : The Franco-American mobilisations, the guardian powers of the North Atlantic Treaty Organization (NATO), alongside the Sahel states victims of terrorism, were initially welcomed with enthusiasm as humanistic initiatives. But their futility in the face of the resurgence of the terrorist threat, the selective battle engaged against the terrorist groups by their troops, the injunction made to the said states not to supervise their territories except under condition, and with the authorization of the rescue forces, among others, would have ended up revealing the the semblance of humanism with which they were adorned. For this , Rejecting the pessimism that enclines to think that the Sahel states would be condemned to share their survival between western assistance and the persistence of terrorism, ( implying in our view the acceptance and of hypocritical geopolitics), this contribution aims to outline the prospect of an effective counterterrorism struggle, within the said states, by inversely mobilizing the endogenous forces both at the state-national level and at the African continental level, assisted in this by new partnership in the light of an intelligent geopolitics.